Pengaruh Green Innovation terhadap Firm Value dengan Environmental Management Accounting sebagai Variabel Intervening - Roza Mulyadi; Maulana, Rizki (Universitas Nahdlatul Ulama Surabaya, 2022)
This study aims to analyze the effect of Green Innovation (GI) on Firm Value (FV) with Environmental Management Accounting (EMA) serving as an intervening variable. The population of this study includes manufacturing and primary sector companies listed on the Indonesia Stock Exchange during the period 2014–2019. Using the purposive sampling method, 30 companies that met the research criteria were selected as samples. Secondary data were obtained from the official website of the Indonesia Stock Exchange. The analytical method used in this study is multiple linear regression analysis, processed with IBM SPSS 22. The results show that Green Innovation has a positive effect on Environmental Management Accounting, as indicated by a significance value of 0.000, which is below the 0.05 level. However, Green Innovation does not have a positive effect on Firm Value, with a significance value of 0.711, which is above the 0.05 level. In contrast, Environmental Management Accounting has a positive effect on Firm Value, with a significance value (ρ-value) of 0.000, which is below 0.05. Furthermore, Environmental Management Accounting mediates the relationship between Green Innovation and Firm Value, as evidenced by a significance value (ρ-value) of 0.000, indicating a significant indirect effect.